SUBJECTIVE WELL BEING PADA “BUJANG TUA” MUSLIM (DEWASA MADYA) - Rita Rita; Zaharuddin Zaharuddin; Ruri Fitriyani (Psikis : Jurnal Psikologi Islami, 2019)
This study discussed about subjective well being in old moslem (middle-adulthood). This research uses descriptive qualitative research method. Data collection techniques used observation, interview, and documentation techniques. The purpose of this study is to find out more about the description of subjective well being in old moslem (middle adulthood). Subjects in this study consisted of four unmarried middle adulthood Muslim subjects who lived in the village of Cupat Parittiga district, West Bangka. From the results of this study it can be concluded that each subject has a picture of subjective well being in old moslem that can be seen from two cognitive and affective processes. From the cognitive aspects that most affect the subject is the status of marriage, daily activities, experiences, socialization, life satisfaction, and hope for the future. From the affective aspect of feeling less satisfied with life, not angry when the status.